A case of facial cutaneous B-cell pseudolymphoma - Junhao CHEN; Xin TIAN; Yi ZHANG; Aili GAO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
A case of facial pseudolymphoma was reported. A 50-year-old female patient presented with invasive pale erythema on the left cheek for 3 months. Dermatological examination: an invasive erythema was seen on the left cheek, which was ill-defined with slightly elevated surface. Histopathology showed clumpy infiltration of lymphocytes and plasmacytes, and the germinal structure of lymphoid follicle was observed. According to immunohistochemistry, there were sporadically CD3 positive T cells, lumpily CD20 positive B cells, intact, sporadically individually CD21 positive FDC structure, and sporadically individually CD1a and CD68 positive cells. The patient was diagnosed with Cutaneous B-cell pseudolymphoma. Triamcinolone acetonide was injected locally, and 0.1% tacrolimus ointment was applied topically. The skin lesion gradually subsided. After 3 months of treatment, the skin lesion subsided, and no recurrence was seen in the six-month follow-up.